Ambonsche Studiefonds and Sarekat Ambon as Forums for Moluccan Nationalists to Initiate Indonesian Independence Movement - Touwe, Sem; Manik, Kresna; Lasaiba, Mohammad Amin; Pattiasina, Johan (Indonesian Historical Studies, 2024)
This research examines the role of the Ambonsche Studiefonds and Sarekat Ambon organizations in fostering nationalism among Maluku natives and in the struggle for Indonesian independence. Using the historical method, this research explores how the Ethical Policy introduced by the Dutch East Indies government influenced the emergence of pro-independence organizations and how they played a role in mobilizing resistance to colonialism. The Ethical Policy, motivated by the Dutch' debt of honor' towards its colonies, opened up access to education for natives and indirectly encouraged national consciousness. The results show that the Ambonsche Studiefonds played a role in expanding access to education for Maluku natives, thus increasing nationalist awareness among them. In addition, Sarekat Ambon became an essential forum for resistance after the transfer of its headquarters to Surabaya, which contributed to the struggle for Indonesian independence. This research also highlights the existence of the Malukan nationalist movement despite many of its members being victims of torture by the Japanese occupation army. Their loyalty and fighting spirit ultimately contributed to Indonesia's independence in 1945. Based on the findings in the heuristic process, this research emphasizes the importance of understanding and appreciating the role of Malukan nationalists in the history of Indonesia's independence struggle. It is hoped that the results of this research can inspire the younger generation to uphold the spirit of nationalism and national unity in facing contemporary challenges.